An etymological, bilingual dictionary esoteric or essential - Zorc, R. David (Philippine Journal of Linguistics, 1979)
It is the purpose if this paper to outline the basic features of an etymological dictionary for use in a bilingual context. Such a dictionary must contain all the information required of a basic dictionary, and it must further act as a guide to speakers of language A (Lg-A) concerning the cultural contexts and histories of words in language B (lg-B). The development of such dictionary involves the authors directly in areas of language planning and the hotly debated issues of descriptive versus prescriptive linguistics. While the development of such dictionary is not an early item on the agenda in the establishment of a bilingual/bicultural programme, the wealth of historical information it can provide - and the pride in one's own cultural language it cana achieve - moves it from (what some have called)'an esoteric luxury ' to a committed essential. Since the author is currently involves in preparing a core etymological dictionary of Pilipino at the request of the Linguistic Society of the Philippines, examples will be drawn from this project (of necessity involving Indonesian languages as well) and also from Australian Aboriginal languages (particularly of the Yolnu group, e.g., Gumatj)